Locked Doors - Ahmad, Misbah (Satura, 2022)
“No one should die near Eid days,” I climbed up on the charpoy to sit near her while taking the bowl of hot halwa out of my mother’s hands, who, with her stare, told me that I had, yet again, uttered words that I should not have. But ignoring that long and discontented stare, I continued to deliver my thoughts on the funeral announcement just made through the mosque loudspeaker. “It ruins Eid for their loved ones forever. Every year twice, near Eid, their happiness would be overshadowed by the loss.”